Should Mergers be Controlled? - Sven-Olof Fridolfsson; Johan Stennek (The Research Institute of Industrial Economics (IUI), 2000)
Anticompetitive mergers benefit competitors more than the merging firms. We show that such externalities reduce firms' incentives to merge (a holdup mechanism). Firms delay merger proposals, thereby foregoing valuable profits and hoping other firms will merge instead - a war of attrition. The final result, however, is an overly concentrated market. We also demonstrate a surprising intertemporal link: Merger incentives may be reduced by the prospect of additional profitable mergers in the future. Merger control may help protect competition. Holdup and intertemporal links make policy design more difficult, however. Even reasonable policies may be worse than not controlling mergers at all.
Keywords: C78; L12; L41; 330; Endogenous Mergers & Acquisitions; Coalition Formation; Competition Policy; Fusionskontrolle; Unternehmenskooperation; Externer Effekt; Wettbewerb; Unternehmenskonzentration; Theorie